Lecanicillium araneogenum sp. nov., a new araneogenous fungus - Chen, Wanhao; Han, Yanfeng; Liang, Zongqi; Jin, Daochao (Phytotaxa, 2017)
During a survey of araneogenous fungi from Guiyang, Guizhou, China, a new species, Lecanicillium araneogenum, was isolated from a spider. It differs from other Lecanicillium species by its spider host, and cylindrical conidia. Multi-locus (TEF, RPB1, RPB2, LSU and SSU rRNA) phylogenetic analysis confirmed that L. araneogenum is distinct from other species. The new species is formally described and illustrated, and compared to similar species.